STUDI LITERATR REVIEW: ASOSIASI POLIMORFISME GEN INTERFERON GAMMA +874 A/T TERHADAP PASIEN SKIZOFRENIA - Agnes Felicia Lubis; Eddy Mart Salim; Abdullah Sahab; Zen Hafy (Universitas Hang Tuah, 2022)
Schizophrenia is an acute and chronic psychiatrist with many environmental and genetic determinants. Some reports suggest that it plays an important role in the regulation of the immune system in the cause of schizophrenia. The evidence collected shows a link between schizophrenia and psychopathology and decreased cytokine production. Interferon gamma +874 A/T gene polymorphism located at base tide to +874. Purpose: This literature review aims to identify polymorphism of the Interferon Gamma +874 A/T gene in Schizophrenia patients. Method: Design research is literature review. Literature searches are conducted by conducting international and national journal searches. The search results of the articles on the database were found as many as 32 articles. The number of articles that fit the inclusion criteria is as many as 28 articles. The results of the literature review obtained 5 journals that discuss polymorphism gene Interferon Gamma +874 A/T in pasein schizophrenia. The 5 journals are case study research. Result: From the articles that have been discussed, it can be concluded that the first 874+ polymorphisms of the interferon gamma gene are associated with the production of this compound. The presence of the AA genotype is associated with a decrease in cytokine production, and the AT genotype is associated with moderate cellulose production and high TT as well as cell production.